2003
DOI: 10.1189/jlb.1102565
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine receptor expression and chemotactic responsiveness of human monocytes after influenza A virus infection

Abstract: Chemokines and their receptors play an important role in site-directed migration and activation of leukocytes. To understand how viral infections may impair this function, we analyzed chemokine receptor expression and responsiveness of human monocytes after infection with influenza A virus. Whereas treatment with infectious virus induced a rapid down-regulation of the CCL2/monocyte chemoattractant protein-1 (MCP-1)-specific receptor CCR2, inactivated virus did not significantly alter CCR2 surface expression. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 34 publications
1
27
1
Order By: Relevance
“…Most importantly, we identified that DI cells recruited by overexpression of Ccl2 play a role in clearance of apoptotic cells and promote resolution of inflammation after noninfectious lung injury. Previous reports demonstrated that CCL2 was upregulated during infectious (42) and noninfectious lung injury (5,10,41,52). CCL2 has been showed to induce leukocyte infiltration during inflammation (8,38,39,43).…”
Section: Discussionmentioning
confidence: 93%
“…Most importantly, we identified that DI cells recruited by overexpression of Ccl2 play a role in clearance of apoptotic cells and promote resolution of inflammation after noninfectious lung injury. Previous reports demonstrated that CCL2 was upregulated during infectious (42) and noninfectious lung injury (5,10,41,52). CCL2 has been showed to induce leukocyte infiltration during inflammation (8,38,39,43).…”
Section: Discussionmentioning
confidence: 93%
“…After 3 min, cells were lysed using a protein extraction reagent (M-PER, Pierce Biotechnology), supplemented with a protease inhibitor mixture (Complete, Roche Diagnostics). Phosphorylation of Akt was then assayed by Western blot as recently described (21). Equal loading was controlled by detecting total Akt.…”
Section: Methodsmentioning
confidence: 99%
“…Infection with Influenza A Virus-Influenza A/PR/8 (H1N1) virus was propagated and purified as previously described (21,22). Viral titers were determined by plaque assay, and monocytes were infected with H1N1 virus at a multiplicity of infection of 2.…”
Section: Methodsmentioning
confidence: 99%
“…DC chemotaxis is targeted during immune evasion by vaccinia virus, human cytomegalovirus (HCMV), herpes simplex virus (HSV) and influenza A virus (Humrich et al, 2007;Moutaftsi et al, 2004;Prechtel et al, 2005;Salentin et al, 2003;Varani et al, 2005), but it is not known whether MV modulates these properties too.…”
Section: Hallmarks Of Measles Virus (Mv)-induced Immuno-mentioning
confidence: 99%